Solving the System of Nonlinear Equations of a Thin-Walled Cylindrical Shell - Narkazakovich, Isroilov Sherzod; o‘g’li, Amirov Ikrom Nurali (International Journal on Orange Technologies, 2023)
We write the system of nonlinear equations of a thin-walled cylindrical shell in the following form